2020
DOI: 10.3390/molecules25174000
|View full text |Cite
|
Sign up to set email alerts
|

Milk Authentication: Stable Isotope Composition of Hydrogen and Oxygen in Milks and Their Constituents

Abstract: This paper summarises the isotopic characteristics, i.e., oxygen and hydrogen isotopes, of Slovenian milk and its major constituents: water, casein, and lactose. In parallel, the stable oxygen isotope ratios of cow, sheep, and goat’s milk were compared. Oxygen stable isotope ratios in milk water show seasonal variability and are also 18O enriched in relation to animal drinking water. The δ18Owater values were higher in sheep and goat’s milk when compared to cow milk, reflecting the isotopic composition of drin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

1
17
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 13 publications
(18 citation statements)
references
References 43 publications
1
17
0
Order By: Relevance
“…Several empirical studies have demonstrated the utility of oxygen and hydrogen stable isotope measurements on milk for verifying the origin of milk [1][2][3][4][5][6][7][8][9][10][11][12][13] . In fact, like many other natural products, milk retains its the isotopic features acquired at the time of its production.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Several empirical studies have demonstrated the utility of oxygen and hydrogen stable isotope measurements on milk for verifying the origin of milk [1][2][3][4][5][6][7][8][9][10][11][12][13] . In fact, like many other natural products, milk retains its the isotopic features acquired at the time of its production.…”
Section: Introductionmentioning
confidence: 99%
“…All these studies indicate that the δ( 18 O/ 16 O) and δ( 2 H/ 1 H) values in milk water were isotopically enriched with the heavier isotope relative to cow drinking water. For δ( 18 O/ 16 O), an enrichment of 2-6 ‰ was documented 6,[9][10][11]12 . Seasonal variations in H and O the isotopic composition in milk water have also been observed, with higher values on summer days and lower values during winter.…”
Section: Introductionmentioning
confidence: 99%
“…The authors found that isotopes could distinguish milk products from different regions, except in cases where the feed type, farming environment, and agriculture practice were similar. Hamzić Gregorčič et al [ 3 ] found that δ 18 O values were higher in sheep and goat’s milk when compared to cow milk, reflecting the isotopic composition of drinking water source and the effect of differences in the animal’s thermoregulatory physiologies. Potočnik et al [ 4 ] focused on the determination of δ 13 C in milk fatty acids as a useful biomarker for determining the authenticity and regional traceability of milk.…”
mentioning
confidence: 99%
“…When the δ 18 O value of the diluted must is higher than −5‰, δ 2 H should also be analyzed. The study performed by Hamzić Gregorčič et al [ 3 ] uses δ 18 O values in lactose to identify the adulteration of milk and detection of water addition. The results are promising and indicate that δ 18 O values in lactose can be used as an internal standard in the detection of the illegal watering of milk (>7%).…”
mentioning
confidence: 99%
See 1 more Smart Citation